Case Report: Management of Multiple Deep-Tissue Cellulitis Without Sling Removal After an Anti-incontinence Procedure in a Female With Diabetes Mellitus - Jiang, Hai-Hong; Hu, Sheng-Ping; Bano, Yasmeen; Ji, Ling-Xiao; Zhang, Peng-Fei; Zhou, Kai (Frontiers in Surgery, 2020)
The transobturator suburethral tape procedure is emerging as a preferred surgical option in the management of stress urinary incontinence. This procedure, also called tension-free vaginal tape transobturator (TVT-O) procedure, has fewer risks of injury to the bladder, similar effectiveness, and shorter surgery duration compared with the older tension-free vaginal tape (TVT) procedure. In this study, we report the case of a female patient with type 2 diabetes mellitus who developed emergency ketoacidosis and severe cellulitis after a TVT-O procedure, which was successfully managed without sling removal and open drainage of abscesses after multi-point puncture drainage, guided by ultrasound, and appropriate antibiotic administration. The patient showed appropriate urinary continence with controlled diabetes mellitus 24 months after treatment. In conclusion, cellulitis of the pelvic floor to associated thigh after TVT-O procedure in a diabetic patient can be managed conservatively if confirmed no sling exposure. However, these patients should be closely observed and followed up during the perioperative period, especially for synthetic sling use.